Numerical investigation on the performance of stone columns under raft foundation in soft clayey soils - Danish, Ahmed; Siti Noor Linda, Taib; Tahar, Ayadat; Alsidqi, Hasan (IOP Publishing, 2021)
Stone columns are the most common and effective technique used for enhancing the overall strength and performance of soft soils. They are more effective for moderately lightweight structures. This investigation presents a parametric study of stone columns embedded in ground to strengthen the soft clayey soil under stiff raft foundation. This research is based on a computational analysis by creating a foundation finite element model consisting of a group of stone columns that are mounted under rafting using PLAXIS 3D. A certain range of parameters (for example spacing, diameter and angle of friction of stone columns) is considered and it is concluded that the increase in diameter and angle of friction of stone columns can improve the ultimate load bearing capacity of the foundation system. Furthermore, the failure mechanism of this foundation scheme is analysed and a semi-empirical model for the determination of the bearing capacity ratio (BCR) is developed from the results of the parametric analysis.